MAGNETIC CHARACTERIZATION AND GEOCHEMICAL ANALYSIS OF SEDIMENTS FROM RIVER AROUND SIDENRENG LAKE, SOUTH SULAWESI - Maulana, Rifky
River sediments are the result of a sedimentation process in river from weathering of bedrock or erosion. Environmental changes that occur in river waters can be caused naturally (lithogenic) and human activities (anthropogenic). The problem that usually occurs is the presence of pollutant that is harmful to the environment. Magnetic method is one of the geophysical methods that can be used to detect pollution in the environment, including river area. This method is used because it can distinguish magnetic mineral properties of river sediments with different environmental characteristics. To determine the element or substance can use geochemical method. Geochemical method is amethod that can be used to analyze the concentration of heavy metals in river sediments to determine the environmental quality and sources of heavy metal pollutants. Sidenreng Lake is a lake located in South Sulawesi that often experiences degradation problems every year. The geological conditions in the area are complex and human activities around the river are thought to be the cause of these problems. In this study, the sediment samples used came from three rivers around Sidenreng Lake, namely Salo Sidenreng River, Salo Pokkoto River, and Salo Panreng River. The method used in this study is a magnetic method with measurement of susceptibility and measurement of IRM (Isothermal Remanent Magnetization). In addition, the XRF (X-Ray Fluoroscene) geochemical method is also used. From the results obtained in these measurements it is known that the Salo Sidenreng River has the highest heavy metal content, the Salo Pokkoto River has the highest SIRM value and magnetite mineral abundance, and the Salo Panreng River has the highest susceptibility value.